Accompagnement dans l’apprentissage de l’argumentation par une équipe pluridisciplinaire : quels effets sur les acteurs? - Martine Paindorge; Virginie Lang; Virginie Libante; Pascal Reboul; Bertrand Aigle (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Within the framework of a master’s degree in Biological, Health and Environmental Engineering developed at the University of Lorraine in France, a multidisciplinary team offers first year students a Situational Awareness Activity (AMS). In groups of three or four, the students have to carry out scientific documentation research on a societal subject related to science and develop pro and con arguments that are then presented orally. The pedagogical team accompanies the students throughout the process, with the aim of fostering the integration and success of new students. It is also a question of reinforcing the skills built up in high school, in particular informational skills in order to facilitate the appropriation of university literacy. The article examines the effects of this support system on the students and their tutors. The analysis of the students' results, their answers to a self-evaluation survey and those of the tutors during semi-directive interviews indicate that this AMS contributes to the acquisition of skills and the development of students' autonomy. The teachers report a change of stance in their role as tutors, a change that also transforms their professional practices in other courses.